2002
DOI: 10.1063/1.1466526
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and optical properties of Ba0.8Sr0.2TiO3 thin film

Abstract: Barium strontium titanate ͑Ba 0.8 Sr 0.2 TiO 3 ͒ thin films have been prepared on Pt/Ti/SiO 2 /Si substrates using a soft solution processing. X-ray diffraction and also micro-Raman spectroscopy showed that the Ba 0.8 Sr 0.2 TiO 3 thin films exhibited a tetragonal structure at room temperature. The presence of Raman active modes was clearly shown at the 299 and 725 cm Ϫ1 peaks. The tetragonal-to-cubic phase transition in the Ba 0.8 Sr 0.2 TiO 3 thin films is broadened, and suppressed at about 35°C, with a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 35 publications
(24 reference statements)
3
29
0
Order By: Relevance
“…Another possible reason for larger values of Eg in the amorphous phase is the existence of the density of states as explained by Davis and Mott [18]. The Eg values of this research work and the bibliography of Table 3 were found above some reported [22,23,24].…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Postedsupporting
confidence: 71%
“…Another possible reason for larger values of Eg in the amorphous phase is the existence of the density of states as explained by Davis and Mott [18]. The Eg values of this research work and the bibliography of Table 3 were found above some reported [22,23,24].…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Postedsupporting
confidence: 71%
“…Oscillating transmittance spectra were observed for 200 nm and 400 nm films, suggesting that they have a flat surface and a uniform thickness. [37][38][39] It was also observed that the number of oscillations decreases with decrease of film thickness. Optical absorption edge was observed at wavelength $300-350 nm (see Fig.…”
Section: Optical Characterizationmentioning
confidence: 76%
“…Recently, it was reported that the ferroelectric phase transition in Ba 0.8 Sr 0.2 TiO 3 thin films occurs near room temperature. 7 In a similar way, the substitution of Zr ions on Ti sites changes strongly the character of the dielectric response close to Curie temperature of BaTi 1−x Zr x O 3 bulk ceramics and thin films. 8,9 When the Zr content is higher ͑Ͼ27% ͒, the BaTi 1−x Zr x O 3 ceramics exhibit typical relaxor-like behavior, in which the T c raises with the increase in frequency.…”
Section: Introductionmentioning
confidence: 89%